Technological and Socioeconomic Environment of Yard Long Bean (Vigna unguiculata subsp. Sesquipedalis) In the Humid Caribbean of Colombia - Martínez-Reina, Antonio María; Tordecilla-Zumaqué, Lilibet; Cordero-Cordero, Carina; Grandett-Martínez, Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The yard-long bean is grown in the peasant economy production system. The objective of this study was to obtain basic information about the production and economic returns of the long bean in the Humid Caribbean of Colombia in 2018. There is no evidence of previous work in terms of technological and socioeconomic characterization. The information was obtained through structured surveys applied by a simple random sampling method to 16 o yard long beans producers. Economic returns were calculated using cost patterns and economic profitability analysis techniques. The results show that the producers have 3 to 40 years of experience in growing the yard-long bean. The surface dedicated to the crop varies from 0.2 to 0.5 ha under a system of family and subsistence agriculture. The use of family labor predominates in 75% and 100% of farmers use non-certified seed. About 90% farmers undertake manual control of weeds and 70% undertake chemical control of insects. 86% of the production goes to the local market and 14% to the families' own consumption. The production costs correspond to $ 3,476,914.2 per hectare and the average production is 4,950 kg ha-1. The average sale price corresponds to $ 765 per kilogram, generating a cost benefit ratio of 1.09 in 4 months of the productive cycle and a profitability of 8.9%. Given that investments are low, it is considered an efficient production system, guaranteeing sustainability over time.